2022
DOI: 10.1039/d2sm00015f
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion strength and tractions are mechano-diagnostic features of cellular invasiveness

Abstract: The adhesion of cells to substrates occurs via integrin clustering and binding to the actin cytoskeleton. Oncogenes modify anchorage-dependent mechanisms in cells during cancer progression. Fluid shear devices provide a...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Furthermore, the total contractile force was demonstrated to be related to adhesion strength 60 and the detachment process of metastasis in vinculin associated cell adhesion. 61 These biological processes were always associated with cell spreding. 62,63 In this case, the total force was only related to cell spreading.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the total contractile force was demonstrated to be related to adhesion strength 60 and the detachment process of metastasis in vinculin associated cell adhesion. 61 These biological processes were always associated with cell spreding. 62,63 In this case, the total force was only related to cell spreading.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study found that adherent cells are exposed to a maximum shear stress of 100 mPa at RPM rotation velocities of 60°/s. Interestingly, a recent work studied the shear forces necessary to detach MCF-7 cells, among others, from their substrate [ 38 ]. It was shown that, to detach 50% of the cells, shear stresses of approximately 4.5 Pa were necessary, a value 40 to 50 times higher than those occurring during RPM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Of late, it has been shown with the help of experiments that normal cells, in general, have greater adhesive strengths compared to metastatic cancer cells. 61 Although here we have mainly focussed on the adhesive signature of cancer cells only in order to delineate the effect of electrical actuation on adhesion, it may become extremely interesting to compare the differences in adhesive dynamics of different cell types (healthy vs. cancer cells) under similar field-mediated microflow setups. These differences may become important markers for several applications ranging from cancer cell isolation to determination of mechanical properties of cells based on adhesive responses.…”
Section: Theoretical Insights Into the Adhesive Dynamicsmentioning
confidence: 99%